Impacts of green marketing mix on consumer purchasing behaviour and the moderation of consumer adaptive-innovative characteristics - Mukhzamir , Mahathir (2024)
Environmental concern is at the forefront of social, political, and academic conversation. However, the exponential increase in awareness on the topic is not reflected in the purchasing of environmentally friendly products over the conventional alternative. This study investigates the relationship between the green marketing mix, i.e. Green Product, Green Price, Green Promotion, and Green Place, and consumer purchasing behaviour as well as evaluates the moderating effects of consumer adaptive-innovative characteristics on said dynamic.